2022
DOI: 10.1007/s00436-022-07499-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Eimeria tenella rhoptry protein with a nuclear localization sequence (EtROP30)

Abstract: Rhoptry proteins (ROPs), secreted by specific rhoptry organelles of apicomplexan parasites, are determinants of parasite pathogenesis and sources of vaccine candidates. Twenty-eight ROPs of Eimeria tenella have been predicted by genomic approaches, and in the present study, E. tenella rhoptry protein 30 (EtROP30) was characterized. Subcellular localizations of EtROP30 in sporozoites and merozoites were in the apical complex and rhoptry-like bulb, suggesting that Et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…This is consistent with the findings by Burrell et al., that although rhoptries predominantly localize at the apical end of sporozoites, they are also present at the central and posterior parts of the cell ( 28 ). This Et ROP21 immunolocalization in E. tenella sporozoites was consistent with previous reports on the immunolocalization of Et ROP30 and Et ROP35 ( 16 , 18 ). Rhoptries are club-shaped organelles that contain a rounded bulb region and an elongated neck region.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with the findings by Burrell et al., that although rhoptries predominantly localize at the apical end of sporozoites, they are also present at the central and posterior parts of the cell ( 28 ). This Et ROP21 immunolocalization in E. tenella sporozoites was consistent with previous reports on the immunolocalization of Et ROP30 and Et ROP35 ( 16 , 18 ). Rhoptries are club-shaped organelles that contain a rounded bulb region and an elongated neck region.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, several T. gondii ROPs, including TgROP1, 5, 7, and 17, have been reported to effectively stimulate protective immunity and to significantly reduce brain cyst loads in immunized animals (11)(12)(13)(14). Several E. tenella ROPs, including Etrop5405, Etrop5905 (EtROP35), Etrop27705 (EtROP30), and Etrop5190 (EtROP17) have been also reported to effectively stimulate protective immunity and reduce oocyst output in immunized chickens (15)(16)(17)(18). In this study, we identified EtROP21, an E. tenella ROP protein, and investigated its localization in sporozoites, as well as its protective efficacy against E. tenella infection.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only EtROP1 has been functionally characterized and associated with parasite survival ( 26 ). Other ROPKs, EtROP30 (ETH_000027705), EtROPK-Eten5-A (ETH_00005405), EtROP35 (ETH_000005905), and EtROP1 (ETH_00005190), have been only partially studied for their immunogenicity ( 22 , 43 45 ). ROPK expression is still poorly described in E. tenella , with only two ROPKs identified in the sporozoite proteome, which we named EtROP1 and EtROP2 ( 25 ), without any clear orthologs in T. gondii , and seven in the merozoite proteome, encoded by ETH_0000075, ETH_0005400, ETH_0005840 , EtROP35 , ETH_00026495 , ETH_00027695 and ETH_00028765 ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 6700 genes have been reported to be expressed across the four developmental life stages (unsporulated oocysts, sporulated oocysts, sporozoites, and merozoites) of E. tenella ( Reid et al., 2014 ). A number of novel antigens, including parasite surface proteins such as Immune Mapped protein-1 and apical membrane antigen-1, and parasite internal antigens, such as microneme (MIC2/MIC3/MIC8), rhoptry (ROP17/ROP30/ROP35), and refractive proteins (SO7) ( Dalloul et al., 2005 ; Konjufca et al., 2008 ; Huang et al., 2018 ; Liu et al., 2020 ; Ma et al., 2021 ; Zhao et al., 2021 ; Bingxiang et al., 2022 ; Liu et al., 2022 ; Wang et al., 2022 ), have been identified as potentially efficient recombinant vaccines. However, there are no reports on the immunoprotective efficacy of VPS against coccidiosis.…”
Section: Discussionmentioning
confidence: 99%